Uptake of cervical cancer screening and its determinants in Africa: Umbrella review - Berihun Agegn Mengistie; Mihret Melese; Ashebir Mamay Gebiru; Mihret Getnet; Amare Belete Getahun; Worku Chekol Tassew; Mikias Mered Tilahun; Yosef Belay Bizuneh; Habtu Kifle Negash; Nebebe Demis Baykemagn; Desale B. Asmamaw; Amlaku Nigusie Yirsaw; et al. (PLoS ONE, 2025)
Background Cervical cancer is the fourth most prevalent type of cancer in women globally. Early detection and treatment of precancerous cervical lesions and human papillomavirus (HPV) infection are strongly advised to decrease the incidence of cervical cancer and death. Cervical cancer is a major public health concern in low- and middle-income nations, where screening and treatment options are constrained. Thus, the main objective of this umbrella review was to determine the pooled uptake of cervical cancer screening and its determinants in Africa. Methods This study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The protocol for this umbrella review was registered on the International Prospective Register of Systematic Reviews (PROSPERO) with reference number CRD42024518297. We conduct a systematic and comprehensive search by using Google Scholar, PubMed, Scopus, Hinari, and Science Direct, from January 1, 2014, to September 20, 2024. The data were extracted using Microsoft Excel spreadsheet. The methodological quality of the included studies was examined using A Measurement Tool to Assess Systematic Reviews 2 (AMSTAR 2). The statistical analysis was carried out using STATA version 17, which includes descriptive analysis, forest plots for prevalence, funnel plot, and an Egger test to examine publication bias. A random-effects model was used to determine the pooled effect estimate. Publication bias was checked by using the funnel plot and Egger’s tests. Results This umbrella review included 11 systematic reviews and meta-analysis studies across Africa with a total of 143,327 study participants. The overall prevalence of cervical cancer screening practice in Africa was 20.94% (95% CI: 15.84%–26.04%). Women’s level of knowledge (AOR: 3.22, 95% CI: 1.64–6.33), positive attitude toward CCS (AOR: 2.48, 95% CI: 2.18–2.81), perceived vulnerability to cervical cancer (AOR = 3.57, 95% CI: 2.75, 4.63), and history of STIs (AOR = 4.89, 95% CI: 3.14, 7.62) were significantly associated with cervical cancer screening practice. In conclusion, the combined estimate of cervical cancer screening use in Africa remains much lower (20.94%) than the World Health Organization (WHO) recommendations target (70%). It indicates that there is a large gap that requires being addressed in collaboration to reduce the burden of cervical cancer and its morbidity and mortality across the continent. Therefore, healthcare professionals, policymakers, and other stakeholders shall implement effective strategies such as empowering women, improving the knowledge and attitude towards cervical cancer screening, advocacy, and expanding screening programs to all eligible women to increase utilization of cervical cancer screening.